Estudos da fotodegradação em compostos estabilizados de ABS ocasionada por ensaios de envelhecimento natural e acelerado - Bosquetti, Péricles (2012)
This work has made comparative assessments of the performance of ABS compounds in accelerated aging and natural exposure tests. The degradation was analyzed by measurements of the Color Variations (CIELab system), Brightness (60º) and Yellow Index (Index), besides the mechanical properties of traction and impact. These characterizations were related to the chemical composition of the ABS polymers and their structural characteristics, such as: free and total SAN contents, succulent phase grafting index and particle size distribution. Different ABS compounds formulated with the same pigments and additives were used, changing the amounts and type of stabilizers used. Some of the compounds have a primary antioxidant and a HALS such as Johoku's JF-90. In another system a HALS (Tinuvin 622) and a UV absorber (Tinuvin P) were used in addition to the primary antioxidant. These compounds were evaluated with 5 and 10% of a high flow SAN, to evaluate the effect of the degradation with the decrease of the rubbery phase of these compounds. In general, the compounds presented excellent physico-mechanical performance, with only mild surface changes over the exposures, even in QUV-B. The HALS efficiency was proportional to the amounts used, since the compounds with the lowest initial yellowing showed better results in the degradation rate, which was related to the use of higher HALS content in the formulation, since the other components were not altered. The HALS were more efficient at surface degradation when compared to the HALS system and UV absorber, without observing synergistic effect of stabilizers for the compounds. The rubbery phase content of ABS interferes with the degradation, since AG1000 compounds, with higher rubber content, presented higher degradation than AF3500, even with higher HALS content in the compound. The addition of SAN up to 10% showed less yellowing and less loss of mechanical properties, such as impact resistance, especially in ABS AG1000.